A band notch rectangular patch UWB antenna with time domain analysis - Nagalingam, Manimaran (Asian Research Publishing Network, 2016)
Design and construction of band notch microstrip Ultra-wideband (UWB) antenna is proposed. As the WLAN 802.11a operates ranging from 5.15GHz to 5.35GHz and 5.725GHz to 5.825GHz. In contrast, HIPERLAN/2 operates ranging from 5.15GHz to 5.35GHz and 5.47GHz to 5.725GHz. Therefore, a band notched filter is required in order to reduce potential interferences between the UWB antenna and WLAN or HIPERLAN/2 bands. The proposed UWB antenna has capability of notching these operating frequencies approximately around 5GHz to 6GHz. The antenna parameters in frequency domain analysis have been investigated to show its capability as an effective radiating element. Furthermore, time domain Gaussian pulse excitation analysis in UWB systems is also demonstrated in this paper. As a result, the simulation results demonstrated reasonable agreement with the measurement results and good band notched ultra-wideband linear transmission performance has also been achieved in time domain.